Entrepreneurial intentions among postgraduate students of UUM - Mohd Asyraf, Ahmad (2015)
The main purpose of this study is to analyze the entrepreneurial intention of postgraduate students of Universiti Utara Malaysia (UUM). The study is coherent with the effort to encourage the involvement of Malaysian in starting a business. Therefore, the study used the Theory of Planned Behaviour by Ajzen (1991) to identify the factors that influence the entrepreneurial intention among postgraduate students of UUM. 370 respondents comprising masters, DBA and PhD students were involved in this study. Using survey method, 370 questionnaires were distributed and only 352 responses were analyzed to test the hypothesis, hence achieve the objectives of the study. The findings show that attitude toward entrepreneurship, perceived behavioural control and subjective norms have positive relationship with entrepreneurial intention among postgraduate students of UUM. Based on the regression analysis, PBC is the strongest predictor for entrepreneurial intention while attitude of students on entrepreneurship is the weakest predictor for their intentions to become entrepreneurs. Further analysis on the differences of student’s intentions to become entrepreneurs between two groups (students with business parents and students with non-business parents) shows a significant result. Students with business parents has higher intention to become entrepreneurs than the other group. The study hopes to assist the responsible parties that involve in the effort to encourage the entrepreneurial activities for example the university in developing and producing more graduates that have high interests on entrepreneurship